An Analysis of the Implementation of Pancasila Values Program at SMP Muhammadiyah 49 Medan - Addawiyah, Robiatul; Hanum, Afifah; Sanjaya, Ilham; Shiddiqi, Zulaqarn Ash (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to analyze the implementation of the Pancasila values program at SMP Muhammadiyah 49 Medan. The research focuses on the strategies, types of activities, teachers’ roles, and challenges faced in instilling Pancasila values among students. A qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The findings indicate that the school has implemented various programs such as flag ceremonies, the practice of discipline, mutual cooperation activities, and the integration of Pancasila values into subjects. Teachers play a vital role as role models and facilitators in the character-building process. However, challenges such as lack of family support, social media influence, and limited facilities still exist. The study recommends the importance of synergy between schools, parents, and communities to strengthen the consistent implementation of Pancasila values.